On the margins of a deanery period (January 1, 2009–June 30, 2013) - Józsa, László (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
As a stroke of luck and as a result of the Senate’s decision, I became dean of the Kautz Gyula Faculty of Economics. This happened at a time when, as a result of the Bologna Process, university education, and within that, economics education, was transitioning to a two-tier system, and the faculty’s doctoral program was becoming more intensive and independent. I would like to present the challenges in four basic points. First, I would like to share a few thoughts on education, which I believe is our most important activity. During my term as dean, we completed the bachelor’s programs in economics and management, international studies, and commerce and marketing, and we launched master’s programs in logistics management, marketing, and leadership and organization. We launched several postgraduate programs and added advanced vocational training to our offerings. Together, these significantly increased the number of students and contributed to the growth in the number of teachers. Under the direction of Professor János Rechnitzer, many of our colleagues obtained doctoral degrees in both regional and business studies at the doctoral school. In order to ensure the quality of education, we limited the number of participants in seminars to 30, and with the help of my secretary, Gabriella Gersei, we tried to relieve the administrative burden on teachers. As a result, the faculty, which showed increasingly better teaching indicators, was included in the forefront of various national lists.